Measuring sentiment orientation and utility in short text messages - Kovács, Balázs; Kruzslicz, Ferenc (Acta Agraria Kaposváriensis, 2011)
The main framework of this paper is the opinion mining, a special area of text mining. The holder of an opinion believes a claim about a topic, and he associates a good or a bad sentiment with his belief. This negative, positive or neutral orientation of the opinion can be detected based on the text messages of the holder. The utility of a comment can be described as the magnitude of the effect of the message on the readers’ opinion. E. g. if a message has higher utility, it has a greater chance to influence the effective demand for a product. So utility is a measure of weighting of messages in calculations. We examined the orientation and utility valuation of short text messages through two methodological approaches: Support Vector Machines (SVM), and Artificial Neural Networks (NN) learning algorithms. We find that the efficiency of the automatic classification of orientation and utility values differs from each other using both methodologies. So we concluded that both of these measures represent different type of connection with the content of the texts. So we examine the opportunity of improving accuracy of classification by including additional measures.